Current approach to adjuvant therapy for breast cancer (a review) - PierFranco Conte (Современная онкология, 2013)
The current approaches to therapy for breast cancer (BC) are based on whether the major markers, such as estrogen receptors, progesterone receptors, and HER2-receptors, are present or absent. Scientific update suggests that subdividing BC into more minor, but distinct subgroups will be continued and treatment approaches will be improved. There is no question that screening and early diagnosis are important in improving treatment results and reducing BC mortality; however, there is increasing evidence for the precedence of adjuvant chemotherapy. Clinical trials show that incorporation of trastuzumab in adjuvant treatment regimens for HER2-positive BC improves substantially long-term results and reduces recurrence rates and the likelihood of a fatal outcome. Of particular interest is the fact that the drugs having different modes of action can produce double inhibition of HER2-receptor. Targeted therapy with trastuzumab in particular has changed dramatically the prognosis of the previously absolutely fatal variant of BC. Combination of targeted therapy will bring the era of personalized medicine closer.